Information Asymmetry in the Information Market: A Narrative Review - Azra Daei; Mohammad Reza Soleymani; Hasan Ashrafi-rizi (Tehran University of Medical Sciences, 2024)
Background and Aim: The role of information in improving the health of society and reducing healthcare costs is undeniable. However, in practice, there exists insufficient and incomplete information among healthcare providers. This lack of comprehensive information among market players leads to inefficiencies and failure in market performance. The main goal of the current research was to investigate health information asymmetry and inadequacy within the health information market. Materials and Methods: This article is a narrative and unsystematic review. Studies were retrieved from the Scopus, PubMed, Web of Knowledge, Magiran, Sid and Google Scholar databases by using the keywords of information inadequacy, Asymmetry of health information done in the fields of article title, abstract and keywords. Subsequently, according to the purpose of the study, the researchers selected relevant resources and summarized their findings. Results: 18 paper were selected for this research. In this research, we specifically address health information inadequacies across three key sections: patients, doctors, and insurance. At the end of each section, ways to solve these deficiencies were mentioned. Results Showed patients faced with the phenomenon of injustice in accessing health information, and the continuation of this injustice leads to the poverty of health information, and due to the lack of proper access to health information, the asymmetry of information between the doctor and the patient was created. Doctors, on the other hand, faced challenges in accessing up-to-date and evidence-based information for patient care. Asymmetric information could be exploited, resulting in induced demand. Insurances face the problems of inappropriate selection, moral hazard and demand induction by the supplier or consumer. Conclusion: Information asymmetry has seriously penetrated the health field and there is a high level of unconfident and uncertainty in it. One of the ways to overcome the health information asymmetry and insufficiency of the health information market is the access of all stakeholders to the information.